Hemodynamics and Wall Shear Stress of Blood Vessels in Aortic Coarctation with Computational Fluid Dynamics Simulation - Gi-Beum Kim; Kwang-Hyun Park; Seong-Jong Kim (Molecules, 2022)
The purpose of this study was to identify the characteristics of blood flow in aortic coarctation based on stenotic shape structure, stenosis rate, and the distribution of the wall load delivered into the blood vessels and to predict the impact on aneurysm formation and rupture of blood vessels by using a computational fluid dynamics modeling method. It was applied on the blood flow in abdominal aortic blood vessels in which stenosis occurred by using the commercial finite element software ADINA on fluid-solid interactions. The results of modeling, with an increasing stenosis rate and Reynolds number, showed the pressure drop was increased and the velocity was greatly changed. When the stenosis rate was the same, the pressure drop and the velocity change were larger in the stenosis with a symmetric structure than in the stenosis with an asymmetric one. Maximal changes in wall shear stress were observed in the area before stenosis and minimal changes were shown in stenosis areas. The minimal shear stress occurred at different locations depending on the stenosis shape models. With an increasing stenosis rate and Reynolds number, the maximal wall shear stress was increased and the minimal wall shear stress was decreased. Through such studies, it is thought that the characteristics of blood flow in the abdominal aorta where a stenosis is formed will be helpful in understanding the mechanism of growth of atherosclerosis and the occurrence and rupture of the abdominal aortic flow.